The Importance of Job Satisfaction in Dubai Police and Influencing Factors - Mohammad, Fatma; Essa, Roudha (Journal of Public Policy and Administration, 2024)
Purpose: Government employees, like persons in the private sector, spend a lot of their time in public service. Consequently, employee satisfaction is essential for safeguarding long-term effectiveness and efficiency in both private and public sector organizations. Creating satisfactory working environments improves employees' work-life balance, thus higher satisfaction levels. Every year, job satisfaction levels are measured throughout all the UAE public sector institutes. This is done through a survey sent by the Dubai Government Excellence Program (DGEP) to the employees every year. With the United Arab Emirates being heralded as one of the leading countries to create ideal work environments for employees, this study aims at determining the underlying factors that affect employee satisfaction in Dubai Police traffic department. Methodology: The study adopted descriptive research design. The research applied a purposive simple random sampling technique and probabilistic sampling technique. Data was collected on Dubai police traffic department employees. A quantitative and qualitative data analysis was conducted for the current research based on the collected data from the questionnaires circulated within the employees of police traffic department. Data were then analyzed using the Statistical Package for Social Sciences (SPSS-15) for statistical analysis. The results were presented in form of tables. Findings: While the socio-demographic factors could be considered factors explaining job satisfaction, age and marital status are the only factors that strongly explain the relationship due to their significant result. Additionally, for the nine environmental factors, using factor analysis to determine variables that strongly explain the dependent variables, the variable under "my work directly contributes towards organization's goals" efficiently explains the status of job satisfaction. Furthermore, execution of mandates informed by the ability of the company to address public complaints and safe work environment influences job satisfaction levels. Unique Contribution to Theory, Practice and Policy: Although salary and work directly contribute towards an organization's goals, companies can ensure that job levels are acquired in the right way. This way, the organization can efficiently address public complaints and promote a safe and healthy working environment. , these findings will inform further studies on behavioral management and workplace productivity in organizations